Analysis Contribution of The Agricultural Sector and The Potential For Economic Growth In Regional Development Planning In West Java Province - Nurul Arifah Fauzi; Hilmy Awalu Faizien (PT. Publikasiku Academic Solution, 2024)
Economic growth prioritizes building and strengthening sectors in the economic field by developing, improving and maximizing resources. The indicator used to see the macroeconomic conditions in a region is by looking at the Gross Domestic Product (GRDP) in the region. The purpose of this study was to determine the agricultural sub-sector included in the leading sector (base) and to determine the shift of the agricultural sub-sector in West Java Province and the classification of Klassen typology in the economic sector in West Java Province. This study uses secondary data in the form of the value of the Gross Regional Domestic Product of West Java Province and the Indonesian Gross Domestic Product at constant 2010 prices by business field from 2019 to 2023. The data is processed using location quentient (LQ) analysis tools, shift share analysis (SSA) and Klassen typology analysis. The results of the location quentient (LQ) analysis show that the Agriculture, Forestry and Fisheries sector is a non-base sector in West Java Province. The results of shift share analysis (SSA) show that the Agriculture, Forestry and Fisheries Sector has a positive influence on regional economic growth (Nij) of Rp. 12,925 billion, Industry Mix (Mij) of Rp. -5,183 billion and competitive advantage (Cij) of Rp. 910,074 billion. The results of the Klassen typology analysis show that the Agriculture, Forestry and Fisheries Sector is a developed but depressed sector, so it is hoped that the West Java Provincial Government will accelerate growth by increasing output and absorbing more labor.